2022
DOI: 10.1002/dev.22270
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating visuomotor coordination in children with amblyopia

Abstract: Past research has reported deficits on reaching and grasping tasks in adults with amblyopia and degraded stereoacuity, but less is known about visuomotor deficits in children-specifically, for complex tasks that require movement sequencing. This study therefore compared the visuomotor performance in 21 children with abnormal binocular vision (patient group) due to amblyopia and/or strabismus to that of 236 children with normal binocular vision development (control group) ages 5-14 years. Visual acuity, stereoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…Previous work has also revealed an association between horizontal fusional reserves with a higher reach peak velocity, as well as an association between accommodative function and the duration of placing the bead on the needle [21]. Analogous findings have been reported in children with amblyopia and/or strabismus, where reduced stereoacuity has been associated with longer grasping and object placement [22]. Interestingly, the reach component seemed less affected in that cohort.…”
Section: Discussionsupporting
confidence: 73%
“…Previous work has also revealed an association between horizontal fusional reserves with a higher reach peak velocity, as well as an association between accommodative function and the duration of placing the bead on the needle [21]. Analogous findings have been reported in children with amblyopia and/or strabismus, where reduced stereoacuity has been associated with longer grasping and object placement [22]. Interestingly, the reach component seemed less affected in that cohort.…”
Section: Discussionsupporting
confidence: 73%
“…Crucially, children with residual stereoacuity performed similarly to the control group on the reaching component, but grasp errors were still evident. Analogous results were found in a study with a different cohort of children (5–14 years old) who showed persistent deficits in grasping that were correlated with stereoacuity [150]. Finally, improvement in manual dexterity was found in children who completed a treatment that targeted binocular function [151].…”
Section: The Effect Of Amblyopia On Upper Limb Movement Controlsupporting
confidence: 53%
“…Efficient use of visual feedback is the hallmark of limb-target control, and binocular stereopsis may be crucial to optimize this mode of control. Because limb-target control matures later, it might be expected that reduced or absent sensory fusion would be associated with deficits in reach-to-grasp coordination in older children and adolescents [149,150]. Crucially, current clinical assessments of fine motor skills do not provide insight into which aspects of control are affected; therefore, it is important to develop novel tools that would allow better understanding of impairments in the sensorimotor control mechanisms.…”
Section: Implications For Assessment and Rehabilitationmentioning
confidence: 99%
“…The VN‐SMN internetwork FC is disrupted in IE patients, of which the defects occur in the early postnatal period and persist across the infancy and early childhood, showing a characteristic developmental trajectory with age. The interaction between VN and SMN is implicated in visuomotor coordination (Burgos et al., 2018 ; Hou et al., 2022 ), thus, impairment in VN‐SMN internetwork FC could account for the observed hand‐eye coordination disorder in IE patients. As a higher‐order functional network, SN is considered to be implicated in integrating external and internal information, attaching salience weighting to different events, regulating the response of other networks to external stimulus or internal physiological signal, coordinating the correlation between functional networks (e.g., DAN‐DMN) (Gao et al., 2013 ; Gao et al., 2017 ; Seeley et al., 2007 ).…”
Section: Discussionmentioning
confidence: 99%